The relationship between career interests and STEM careers of secondary school students - Mahmud, Mohd Izwan; Puad Mohd Kari, Dharatun Nissa; Tee, Yin Ai (ASR Research India, 2022)
Career choice is important and usually be influenced by knowledge and environmental factors during the career choice process. This study aimed to identify the STEM career interest tendencies of Form 3 students and measure the correlation between career interests and STEM careers. The study design was a quantitative survey study. Participants consisted of 329 students aged 15 years old; 140 males and 189 females. The instruments used in this study were questionnaires related to individual profiles, STEM semantic survey, and Career Interest Inventory (IMK). Data were analyzed using SPSS Windows version 23.0 to obtain the descriptive and inferential statistics. The findings of the study indicated Holland’s three-point code for STEM careers was Investigative-Conventional-Social (I-C-S). The findings showed that students were more likely to choose Investigative interest and Science careers. The level of students' perception of STEM careers was at a high level. The result of chi-square analysis, χ2 = 50.509 and p-value = 0.000. The study conducted had shown that Form 3 students had an I-C-S personality pattern that was consistent with the STEM career profession. The implications of this study for career counselors are to ensure that career interest tests were used to help students make career choices and decisions more confidently and responsibly.